What impacts the acceptance of e-learning through social media? An empirical study - Abd. Ghani, Prof. Madya Dr. Mazuri (Springer Science and Business Media Deutschland GmbH, 2021)
An incredible volume of research was conducted to examine the students’ acceptance of e-learning systems through the platforms of higher education institutions (HEIs). However, little debate was made concerning the exploration of the factors influencing the acceptance of e-learning systems via social media applications. Accordingly, this study extends the technology acceptance model (TAM) with social media practices, including knowledge sharing, motivation and uses, and social media features to understand the impact of these determinants on students’ acceptance of elearning systems. The partial least squares-structural equation modeling (PLS-SEM) along with the importanceperformance map analysis (IPMA) are employed to analyze the theoretical model using survey data collected from 410 students. The findings indicated that knowledge sharing, motivation and uses, and social media features have significant positive effects on both perceived ease of use (PEOU) and perceived usefulness (PU). It is also essential to report that the e-learning system acceptance is positively affected by PEOU and PU together. Further, the IPMA results showed that PEOU was the most important influential factor of e-learning systems acceptance. © Springer Nature Switzerland AG 2021.